ANALYSIS OF THE GESTALT APPROACH IN INCREASING ADOLESCENT CONFIDENCE - Aqima Sholehati; Netrawati (Yayasan Citra Dharma Cindekia, 2021)
The basic goal of Gestalt therapy is to increase awareness, which in itself is seen as curative or growth-producing. Awareness requires self-knowledge, responsibility for choices, contact with the environment, immersion in the stream of experience, self-acceptance, and the ability to make contact. The research method used is a literature review which is supported by data from several articles, source books, and other supporting documents. Guidance and counseling teachers can apply group counseling services to address career problems. One approach that can be used to help adolescents approach themselves is an approach that focuses on gestalt techniques. The results showed that counseling services with a gestalt approach could help in increasing adolescent self confidence.